Effect of KIOM-79 on Diabetes-Induced Myocardial Fibrosis in Zucker Diabetic Fatty Rats. (13th November 2013) - Kim, Junghyun; Sohn, Eunjin; Kim, Chan-Sik; Lee, Yun Mi; Jo, Kyuhyung; Kim, Jin Sook
Abstract : KIOM-79, a herbal mixture of parched Puerariae radix, gingered Magnoliae cortex, Glycyrrhizae radix, and Euphorbiae radix, has a strong inhibitory effect on advanced glycation end products (AGEs) formation. We investigated the beneficial effects of KIOM-79 on cardiac fibrosis in Zucker diabetic fatty (ZDF) rats. KIOM-79 (50 or 500 mg/kg/day) was orally administered for 13 weeks. AGEs formation and collagen expression in the myocardium were assessed by immunohistochemistry. The expression levels of the receptor for AGEs (RAGE), transforming growth factor- β 1 (TGF- β 1), collagen IV, fibronectin, urotensin II, and urotensin II receptor were examined in the myocardial tissue of ZDF rats. KIOM-79 treatment at 500 mg/kg inhibited the accumulation of AGEs, reduced RAGE mRNA and protein expression, and reduced the upregulation of cardiac fibrogenic factors, such as fibronectin and collagen IV, in heart of ZDF rats. Additionally, KIOM-79 ameliorated urotensin II/receptor gene expression in the cardiac tissue of ZDF rats. Our findings indicate that KIOM-79 diminishes cardiac fibrosis in ZDF rats by preventing AGEs accumulation and RAGE overexpression and by modulating the cardiac urotensin II/receptor pathway, which decreases the amount of profibrotic factors, such as TGF- β 1, fibronectin, and collagen in cardiac tissue.